One dark night : a novel - Richell, Hannah (Atria Paperback, 2025)
"On Halloween, a group of teenage students meet in the woods near Sally in the Wood, a road steeped in local lore and rumored to be haunted by the ghost of a murdered girl. By the end of the night, one student will be dead. Rachel, the school guidance counselor, is trying to keep a handle on her increasingly distant teenaged daughter, Ellie, while students and parents panic and mourn. Her ex-husband and detective Ben, dealing with a personal crisis of his own, has concerns about his daughter's safety as he investigates the death. Meanwhile, Ellie is keeping secrets from both her parents, including one about where she was that night"--